IMPLEMENTATION OF NEURAL NETWORKS AND BOOSTING ALGORITHMS FOR EFFECTIVE INTRUSION DETECTION - Golovko, Vladimir; Vaitsekhovich, Leanid (International Journal of Computing, 2014)
In this article the classification task in the domain of intrusion detection is considered. Often a chosen algorithm is not good enough for practical use. So the question arises how is it possible to improve the performance? In this case we can employ so-called Committee Machines that increase accuracy and reliability of the base classification model. These advantages are the result of dividing complex computational problems among several experts. The knowledge of each expert influences on the general conclusion of Committee Machine.